Professional Competence, Work Discipline, and Work Engagement Affect Teacher Performance: The Mediating Role of Organizational Citizenship Behavior - Murdiansyah Indra Putranto; Rasiman Rasiman; Qristin Violinda (STAI Hubbulwathan Duri, 2025)
Improving teacher performance is critical for advancing education quality, especially in primary schools. While professional competence, work discipline, and work engagement are known to influence performance, the role of organizational citizenship behavior (OCB) as a mediating variable remains underexplored in Indonesian elementary school settings. This quantitative study employed an ex post facto design involving 132 public elementary school teachers in Bulu Subdistrict, Rembang Regency, selected through proportional random sampling. Data were collected using validated questionnaires measuring professional competence, work discipline, work engagement, OCB, and teacher performance. Structural equation modeling with path analysis and bootstrapping (5,000 resamples) was used to examine direct, indirect, and mediating effects. Professional competence (β = 0.278, p = 0.001), work discipline (β = 0.241, p = 0.003), and work engagement (β = 0.334, p 0.001) significantly influenced teacher performance. OCB also significantly predicted performance (β = 0.301, p 0.001). OCB partially mediated the effects of work discipline and engagement on performance but did not mediate the effect of professional competence. The model explained 57.2% of the variance in teacher performance (R² = 0.572), with all fit indices indicating a good model fit. These findings highlight the critical role of OCB in translating discipline and engagement into improved teacher performance. While competence directly enhances performance, fostering an organizational culture that supports OCB is essential for leveraging discipline and engagement into broader professional gains.